Non-similar Keller box analysis of magneto chemically radiative Buongiorno’s nanofluid flows past a stretching surface - Anjum, Asra; Gaffar, Shaik Abdul; Kumar, D. Sateesh; Bég, O. Anwar; Peerusab, Samdani (Journal of Naval Architecture and Marine Engineering, 2024)
A non-similar Keller Box analysis of magnetochemically radiative Buongiorno's nanofluid flows past a stretched surface is presented in this work. It offers insightful information for raising the effectiveness of heat, and mass transmission. Numerous scholars have examined various topics, including radiation, porosity, aligned magnetic fields, mixed convection, and the Forchheimer number when including nanofluids in these flows. However, thermal radiation impact, chemical reaction, and magnetic parameters on Buongiorno’s nanofluid through a stretching sheet do not yet have a mention within existing scholarly works. To fill in this knowledge vacuum and provide insightful information about these variables. The investigation uniquely encompasses coupled magnetic properties, chemical reactions, thermal radiation on heat, mass transmission in nanofluids, assimilating Brownian motion, buoyancy ratio, and thermophoresis, offering a comprehensive multi-physics analysis that was not previously explored. By employing the Keller Box method (KBFDM), after being converted into a set of nonlinear ODEs, from the PDEs that govern the flow analysis are solved numerically, MATLAB is utilized to obtain graphs and tabular values. The effects of elements without dimensions, such as heat radiation (0 ≤ R ≤ 1), chemical reaction (0 ≤ Kr ≤ 5), and magnetism parameter (0 ≤ M ≤ 2) on concentration, temperature, and velocity distributions are discussed. Additionally, Nusselt number, Sherwood number, and Skin friction impacts are demonstrated. Velocity depreciates with elevating magnetic parameters. The velocity field experiences a significant boost in response to rising thermal radiation and chemical reaction values. A greater magnetic field causes the concentration profile to rise steadily of nanoparticles. Moreover, as (Kr) raises steadily, velocity appreciates however, temperature and concentration diminish substantially. When the magnetic parameter (M) rises, the Schmidt number (Sc) and skin friction decay. Skin friction and Sherwood number show an upward trend for myriad increasing values of thermophoresis (Nt). The present study shows a compatibility rate of 99.9% with the previous research across different values of Nusselt (Nu) and Sherwood (Sh) numbers. Significantly, higher (Pr) enhances (Cf) and (Sh) because of thicker thermal and thinner momentum boundary layers, while decreasing the (Nu) to inhibit heat transfer. It is noteworthy that, increasing (Sc) elevates (Cf), (Nu) and (Sh) by enhancing fluid viscosity and reducing mass diffusivity, which causes concentration within BL to thicken, and improves shear stress and heat transfer efficiency. Through this work, significant knowledge concerning how to Boost the productivity of chemical processing and thermal control mechanisms in magnetic, radiative environments involving nanofluids can be gained for industrial processes. Journal of Naval Architecture and Marine Engineering, 21(2), 2024, P: 127- 153